A Study on Girl-Child Participation in Decision Making: A Case of the She Leads Project at Girl up Initiative Uganda - Ritah Patience Ampaire (Uganda Christian University, 2024)
Girls and young women in different areas are left out in decision-making processes. The She Leads project in a bid to ensure that Girls and Young women are actually involved in decision-making focuses on three domains that is institutional, social domain and CSO domain. This study aims at examining and evaluating the performance in the different domains. This study is of good importance to the researcher, girls and young women at the organization, service providers, implementing partners and all the would be readers to understand the impact and influence the She Leads project as an intervention on the effective participation in decision making processes not only to the girls and young women in the organization but also to their families, schools and communities. The study also helped provide a clear insight to the girls and young women on their impact as advocates in challenging negative gender norms and also provide where necessary possible recommendations.